2018
DOI: 10.4240/wjgs.v10.i2.13
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous electroacupuncture alleviates postoperative ileus after gastrectomy: A randomized clinical trial

Abstract: AIMTo investigate the efficacy and safety of transcutaneous electroacupuncture (TEA) to alleviate postoperative ileus (POI) after gastrectomy.METHODSFrom April 2014 to February 2017, 63 gastric cancer patients were recruited from the Second Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, China. After gastrectomy, the patients were randomly allocated to the TEA (n = 33) or control (n = 30) group. The patients in the TEA group received 1 h TEA on Neiguan (ST36) and Zusanli (PC6) twice da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Acupuncture has been used as a minimally invasive and comprehensive treatment for gastrointestinal motility disorders in China for thousands of years. Chen et al [ 7 ] found that transcutaneous electroacupuncture accelerated bowel movements. EA has also been widely accepted by Western clinicians and patients and has become an effective method for the treatment of various gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Acupuncture has been used as a minimally invasive and comprehensive treatment for gastrointestinal motility disorders in China for thousands of years. Chen et al [ 7 ] found that transcutaneous electroacupuncture accelerated bowel movements. EA has also been widely accepted by Western clinicians and patients and has become an effective method for the treatment of various gastrointestinal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of EA in a previous study on gastrectomy was limited. Chen et al [ 7 ] found that transcutaneous electroacupuncture accelerated bowel movements in patients undergoing open gastrectomy but laparoscopic surgery. Meng et al [ 15 ] conducted a study in 90 patients with prolonged POI who were randomly selected and given electroacupuncture or no acupuncture after the operation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 EA was also proved to normalize the impaired colonic motility induced by rectal distension or constipation in animal models. [24][25][26] Recently, a few of clinical studies found that EA at ST-36 accelerates the recovery of gastrointestinal motility after colorectal surgery 20,[27][28][29] As shown by Simon SM Ng, patients who received EA had a shorter time to defecation than patients who received no EA after laparoscopic surgery for colorectal cancer.…”
Section: Electroacupuncture Is the Combination Of The Use Of Traditionalmentioning
confidence: 99%
“…A small number of clinical studies proved that TEA could significantly improve gastric emptying in dyspeptic patients [ 17 ]. Our previous randomized, controlled, single-center study demonstrated that TEA improved bowel movement and alleviated postoperative ileus after gastrectomy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%